Effect of Processed Coffee Husk on Feed Intake, Nutrient Digestibility, Body Weight Changes and Economic Feasibility of Bonga Sheep Fed on Natural Pasture Hay as a Basal Diet - Lidya Marew; Fentahun Meheret; Bimrew Asmare (Veterinary Medicine and Science)
ABSTRACT Background Ethiopia is one of the world's coffee producers, generating about 192,000 metric tonnes of coffee husks annually as by‐products. The material can be used for ruminant diets to improve the nutrient utilisation of animals. However, coffee husk has toxic compounds, which can be minimised through different processing methods. Though the above techniques can minimise the toxicity level of coffee husk and increase the bioavailability of nutrients, there is scanty information on the comparative efficacy of these techniques, especially in ruminant nutrition. Objective The study was conducted to examine the effect of processed coffee husk on feed intake, nutrient digestibility, body weight changes and profitability of Bonga rams based on natural pasture hay. Methods In the experiment, 24 rams were used, and the rams were grouped into six blocks based on initial body weight (mean BW 21.5 ± 1.01 kg). The rams were quarantined for 21 days, and each ram was randomly assigned to one of the experimental feed treatments in a randomised complete block design (RCBD). The experimental treatment feeds include 400 g conventional concentrate mix (CM) containing Noug seed cake and wheat bran (T1); 200 g boiled coffee husk + 200 g CM (T2); 200 g roasted coffee husk + 200 g CM (T3) and 200 g raw coffee husk + 200 g CM (T4). The CM was made in the ratio of 1:1. The data collected from the 90‐day experimental period were: dry matter and nutrient intakes, initial body weight, final body weight and body weight changes. After the growth experiment, a 7‐day digestibility trial was followed by collecting faeces using a harness bag. The data were managed using Microsoft (MS) Excel 2010 and analysed using R software (v. 4.3.2). The chemical compositions of the CM had maximum crude protein (22%), followed by boiled coffee husk (14.74%), which was higher than natural pasture hay (6.91%) and raw coffee husk (12.4%). Results The total dry matter intake (p < 0.05), metabolisable energy, and total nutrient intakes of rams were significantly (p < 0.001) maximised when rams fed on boiled coffee husk (T2) than raw (T4) and roasted (T4) coffee husk, except for NDF and organic matter intakes. The apparent digestibility of nutrients and feed conversion efficiency were maximised for rams assigned to T2. There was maximum daily body weight gain (p < 0.001) when rams were supplemented with boiled coffee husk (T2). Also, body weight changes of rams were significantly (p < 0.001) higher for rams supplementation with boiled coffee husk. Conclusion Therefore, the boiled coffee husk as an alternative feed resource can be replaced by about half of the commercial CM without adverse effects of anti‐nutritional factors and enhance the income of smallholder farmers in the coffee crop‐livestock production system.